Search
Ask a question
0

-(-(-)(-)(-10x))=-5 solve for x

solve for x

3 Answers by Expert Tutors

Tutors, sign in to answer this question.
Jesse S. | Patient and knowledgeable Math tutorPatient and knowledgeable Math tutor
1
-(-(-)(-)(-10x))=-5
-(-(-)10x) =-5
-(10x)=-5
-10x =-5
x=5/10
x=1/2
 
 

Comments

You are right Jesse.  The right answer is 1/2. 
Michael J. | Effective High School STEM Tutor & CUNY Math Peer LeaderEffective High School STEM Tutor & CUNY ...
5.0 5.0 (5 lesson ratings) (5)
0
Since you have an odd number of negative signs on the left side of the equation already, the left simplifies to -10x.  Then, you have 
 
-10x = -5
     x = 1/2
Martin P. | From Educator to EngineerFrom Educator to Engineer
4.9 4.9 (14 lesson ratings) (14)
0
 
-(-(-)(-)(-10x))=-5
 
-(-(-10x))=-5
 
-(10x)=-5
 
10x=5
 
x=2

Comments